KIFC1 aggravates non-small-cell lung cancer cell proliferation and metastasis via provoking TGF-β/SMAD signal: KIFC1 promotes metastasis of NSCLC - Liu, Yafang; Ye, Wei; Miao, Xiaohui; Wang, Xiaoyu (Cellular and Molecular Biology, 2023)
Worldwide, the non-small-cell lung cancers (NSCLC) is considered one of the deadliest cancers. Very early onset of distant metastasis is an important reason for the lower survival rate of NSCLC patients. Kinesin family member C1 (KIFC1) with highly protein levels in various of cancers contributes to the initiation and development of many cancers. KIFC1 has also been suggested as a possible marker of NSCLC. Nevertheless, the effects of KIFC1 on NSCLC metastasis has not been researched. To investigate the role of KIFC1 in NSCLC and related mechanisms. Westernblot and quantitative real-time PCR were conducted to test the levels of KIFC1 in NSCLC cancerous tissues and NSCLC cancerous cell lines. Colony formation assay, CCK-8, transwell assay and wound healing assay was conducted to detect the functions of KIFC1 on proliferation, migration and invasion of NSCLC cell lines. WesternBlot was conducted to test the role of KIFC1in EMT and TGF-β/SMAD pathway. We discovered that the protein levels of KIFC1 were upregulated in NSCLC cancerous cell lines and cancerous tissues from mankind. KIFC1 was positively related with worse clinical staging and lymphnode metastasis of NSCLC patients in clinical data. Overexpressed KIFC1 aggravated expansion, migration and invasion in NSCLC cells, whereas silencing of KIFC1 had the opposite effect in vitro. Mechanistically, the progression of NSCLC was promoted by KIFC1 through induction of EMT and TGF-β/SMAD signal. KIFC1 promoted proliferation and metastasis through accommodating TGF-β/SMAD signal, which is a hint that KIFC1 might offer a prospective therapeutic target for the NSCLC treatment.